2008
DOI: 10.1172/jci34292
|View full text |Cite
|
Sign up to set email alerts
|

A hypomorphic mouse model of dystrophic epidermolysis bullosa reveals mechanisms of disease and response to fibroblast therapy

Abstract: Dystrophic epidermolysis bullosa (DEB) is a severe skin fragility disorder associated with trauma-induced blistering, progressive soft tissue scarring, and increased risk of skin cancer. DEB is caused by mutations in type VII collagen. In this study, we describe the generation of a collagen VII hypomorphic mouse that serves as an immunocompetent animal model for DEB. These mice expressed collagen VII at about 10% of normal levels, and their phenotype closely resembled characteristics of severe human DEB, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
203
1
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(224 citation statements)
references
References 41 publications
10
203
1
10
Order By: Relevance
“…PCR analysis of mRNA extracted from RDEB mouse spleens generated products corresponding to the aberrantly spliced Col7a1 detected in this mouse model (Fig. 2B) (25), and Western blot analysis of protein lysates from RDEB mouse spleens showed barely detectable levels of full-length collagen VII (Fig. 2C), thus collectively validating the expression analysis.…”
Section: Collagen VII Is Present In Lymphoid Conduits In a Unique Prosupporting
confidence: 65%
See 2 more Smart Citations
“…PCR analysis of mRNA extracted from RDEB mouse spleens generated products corresponding to the aberrantly spliced Col7a1 detected in this mouse model (Fig. 2B) (25), and Western blot analysis of protein lysates from RDEB mouse spleens showed barely detectable levels of full-length collagen VII (Fig. 2C), thus collectively validating the expression analysis.…”
Section: Collagen VII Is Present In Lymphoid Conduits In a Unique Prosupporting
confidence: 65%
“…For the studies, samples from human individuals with molecularly confirmed severe generalized recessive RDEB were used, as well as two genetic mouse models, the collagen VII hypomorphic RDEB mouse and a tamoxifen-inducible Col7a1 knockout mouse (1). The RDEB mouse shows all major signs of severe RDEB (25), and the tamoxifen-inducible Col7a1 knockout mouse allows targeted ablation of Col7a1 expression in time and space (1). RDEB is a progressive disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A surviving DEB mouse that was reported recently was the DEB hypomorphic mouse model. 4 These mice, which had about 10% of the normal mouse COL7, did not show the abnormal form and function of anchoring fibrils seen in human patients of RDEB. Second, no studies have examined in detail whether the introduction of the human COL7 gene into DEB mouse cells can rescue the DEB phenotype without causing adverse effects in a living DEB model.…”
mentioning
confidence: 86%
“…However, it is exciting that gene therapy has already been used to repair a laminin-332 (laminin-5) defect in a patient with junctional epidermolysis bullosa (Mavilio et al 2006). Furthermore, a potential alternative to gene therapy may be to restore a functional ECM in blistering disorders by injection of nonmutant fibroblasts (Fritsch et al 2008). Another advance that is highly appealing is to use extracellular matrix biomaterials for skin repair (Cornwell et al 2009;Wolf et al 2009).…”
Section: Looking To the Futurementioning
confidence: 99%